Model of quality of life in a group of people with chronic low back pain - Urszula Ziętalewicz; Kamilla Bargiel-Matusiewicz (Health Psychology Report)
Background Chronic low back pain (CLBP) is one of the leading causes of a reduction in the quality of life (QoL). Various methods ef-fectively improve patients’ performance and coping with their symptoms in the short term. The lack of focus on psychologi-cal factors, thus overlooking an important element of the holistic model, may result in the modest long-term improvement. The present study aimed to test the relationships between the variables in Wilson and Cleary’s QoL model in a CLBP group and to compare them to a nonpain group.